Layout optimization of stratospheric balloon solar array based on energy production - Jiang, Yi; Lv, Mingyun; Wang, Chuanzhi; Meng, Xiangrui; Ouyang, Siyue; Wang, Guodong (Energy (Oxford), 2021)
Solar array plays a decisive role in the energy system of stratospheric balloon. Optimizing the layout of solar array is beneficial to the improvement of energy production, but the research about this subject is rare. This paper established a theoretical model consisting of thermal and energy model, weight/lift equilibrium. A MATLAB computer program is developed to simulate the output power of solar array and the energy harvesting along with connection length and balloon diameter. Through comparative analysis, the theoretical model is proved to be feasible. Further, the effects of connection length, balloon diameter and the ratio of connection length to balloon diameter are discussed in detail. The results show that solar array total output power is sensitive to the variation of the connection length, balloon diameter and the ratio of connection length to balloon diameter. Moreover, the layout of solar array can be optimized though increasing the ratio of connection length to balloon diameter, however, the total output power would not increase when the ratio of connection length to balloon diameter is greater than 1.5. Therefore, Choosing the proper ratio of connection length to balloon diameter might be an effective approach for optimizing the stratospheric balloon energy system. •A theoretical model considering thermal model, energy model and weight/lift equilibrium was proposed.•The theoretical model was proved to be feasible through comparative analysis.•The effects of connection length, balloon diameter and ξ on the solar array output performance were studied.•Increasing the value of ξ is benefit to improve total output power of solar array until it reaches 1.5.